Reka Bentuk Kad Gamifikasi Mudah Kenali Ilmu Hadis Bagi Kursus Ulum Al-Hadith - Siti Mursyidah Mohd Zin; Farhah Zaidar Mohamed Ramli; Suriani Sudi; Phayilah Yama; Siti Rosilawati Ramlan (Penerbit Universiti Islam Selangor, 2026)
Indexed by MYCITE